J. Oskar Andersen 150 år 1866-2016 - de Fine Licht, Christian (Kirkehistoriske Samlinger, 2018)
J. Oskar Andersen underviste i mange år i kirkehistorie ved Københavns Universitet. Han anvendte som noget nyt den kildekritiske metode, han lærte hos historikeren Kristian Erslev. Hans bidrag til udforskningen af dansk reformationshistorie er mange. Desuden fuldførte han Kirkeleksikon for Norden og var blandt meget andet formand for Selskabet for Danmarks Kirkehistorie. Han var en indflydelsesrig kirkepolitiker og medlem af folketinget i mellemkrigstiden. Men i de fleste omtaler af J. Oskar Andersen dominerer hans nederlag i konkurrencen om det kirkehistoriske professorat i 1901. I denne jubilæumsartikel er det hensigten at vise, hvorledes hans livsværk på trods heraf blev omfattende og betydningsfuldt. Summary J. Oskar Andersen (1866-1959) graduated in theology from the University of Copenhagen (1890) and became a lecturer in church history at the same institution, eventually with the title of professor (1913), until retirement in 1936. He pioneered the use of critical methods in his field, doing essential research in Danish reformation studies and publishing essays until 1956. At the same time, he was an influential church politician, becoming a member of the Danish parliament (1918-1939), elected for the conservative party in Frederiksberg, Copenhagen. He edited the Danish Journal of Theology, he published a four volume Scandinavian Encyclopedia of Church and Theology and he was president of a respected Art society. His unlucky attempt at becoming a professor in 1901, which seems to have caused lifelong bitterness, has dominated most biographical descriptions. In this article, it is viewed as the cause of his tireless and mostly successful efforts to secure a respected place in Danish academic life.